«Sempre e mais despois». The Centenary of Borobó’s (Raimundo García Domínguez) Birth - Acuña Trabazo, Ana (Madrygal. Revista de Estudios Gallegos, 2016)
This article focuses on Borobó’s lesser-known works in poetry, theatre, and narrative in Galician. Firstly, we shall look for traces of Mr. Borobó’s presence in the Magazine Madrygal, and then we shall deal with the relationship between this “madrigalego” and the young people that regularly met at the Café Comercial.
Keywords: Raimundo García Domínguez; Borobó; Poetry; Theatre; Narrative; Madrygal; “Sétima”.